Crowd-Sourced Buildings Data Collection and Remote Training: New Opportunities to Engage Students in Seismic Risk Reduction - Antonella Peresan; Chiara Scaini; Carla Barnaba (Earth Science, Systems and Society)
Young generations are increasingly committed to understanding disasters, and are a key player in current and future disaster risk reduction activities. The availability of online tools opened new perspectives in the organization of risk-related educational activities, in particular in earthquake-prone areas. This is the case of CEDAS (building CEnsus for seismic Damage Assessment), a pilot training activity aimed at collecting risk-related information while educating high-school students about seismic risk. During this experimental activity, students collected and elaborated crowdsourced data on the main building typologies in the proximity of their homes. In a few months, students created a dataset of valuable risk-related information, while getting familiar with the area where they live. Data collection was performed both on-site, using smartphones, and online, based on remote sensing images provided by multiple sources (e.g., Google maps and street view). This allowed all students, including those with limited mobility, to perform the activity. The CEDAS experience pointed out the potential of online tools and remote sensing images, combined with practical activities and basic training in exploratory data analysis, to engage students in an inclusive way. The proposed approach can be naturally expanded in a multi-risk perspective, and can be adjusted, eventually increasing the technical content of collected information, to the specific training and expertise of the involved students, from high-school to university level.